1999
DOI: 10.1016/s0008-6363(99)00195-9
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-shift of the current activation in HERG S4 mutation (R534C) in LQT2

Abstract: The data revealed that arginine at position 534 in the S4 region of HERG is indeed involved in voltage-dependence of channel activation as a voltage sensor. Our examination indicated that HERG current suppression in R534C mutation was the least severe among other mutations that have been electrophysiologically examined, while affected patients did show significant QT prolongation. This suggest that another unidentified factor(s) that prolong APD might be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…In 1999, Nakajima et al [14] reported that position 534 in the S4 region of hERG was involved in voltage-dependent channel activation as a voltage sensor. Kinetic analyses revealed that the R534C mutation shifted the voltage-dependent hERG channel activation to a negative direction, accelerated activation and deactivation time course, and reduced steady-state inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, Nakajima et al [14] reported that position 534 in the S4 region of hERG was involved in voltage-dependent channel activation as a voltage sensor. Kinetic analyses revealed that the R534C mutation shifted the voltage-dependent hERG channel activation to a negative direction, accelerated activation and deactivation time course, and reduced steady-state inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is most clearly exemplified by the study of the R534C mutant Kv11.1 channel. When expressed in Xenopus oocytes, the mutation results in an increased open probability, i.e., a gain of function, yet clinically the mutant causes loss of function (434). Subsequently, it was shown that the R534C mutant when expressed in mammalian cells is retained in the ER, explaining the clinical loss of function (19).…”
Section: Abnormal Gatingmentioning
confidence: 99%
“…Like other members of the K v family of potassium channels, hERG channels are activated by membrane voltage by a mechanism that involves the voltage-sensor domains (8)(9)(10)(11)(12). In hERG channels, voltage-dependent gating is regulated by the large, cytoplasmic N-terminal domain (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%